ЭНЕРГОЭФФЕКТИВНОСТЬ СИСТЕМ ЭЛЕКТРОСНАБЖЕНИЯ ПОДВИЖНОГО СОСТАВА МЕТРОПОЛИТЕНА - Жемеров, Г.Г.; Тугай, Д.В.; Холод, О.И. (Інститут електродинаміки НАН України, Київ, 2013)
Comparative assessment of five possible energy supply systems of rolling stock subway is carried out, four of which are an alternative to the existing in Ukraine. The method for evaluation of energy efficiency of power supply systems based on the use of the terms "energy" and "energy losses" is proposed. It is shown, that the use of energy-intensive energy storage in subway power systems will not only reduce the total amount of electricity consumed from the network, but also will reduce the energy loss during its transportation and consumption. References 10, figures 5, table 1.